2006
DOI: 10.1175/jtech1853.1
|View full text |Cite
|
Sign up to set email alerts
|

Passive Acoustic Determination of Wave-Breaking Events and Their Severity across the Spectrum

Abstract: A passive acoustic method of detecting breaking waves of different scales has been developed. The method also showed promise for measuring breaking severity.Sounds were measured by a subsurface hydrophone in various wind and wave states. A video record of the surface was made simultaneously. Individual sound pulses corresponding to the many individual bubble formations during wave-breaking events typically last only a few tens of milliseconds. Each time a soundlevel threshold was exceeded, the acoustic signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 53 publications
3
50
2
Order By: Relevance
“…This tends to overestimate the breaking probability by a factor of 1.5 to 2 (Manasseh et al 2006), compared to the present approach in which we consider that several waves (of different scales) may be present at the same place and time. We shall thus correct for this effect, simply dividing P by 2.…”
Section: Wave Breakingcontrasting
confidence: 68%
“…This tends to overestimate the breaking probability by a factor of 1.5 to 2 (Manasseh et al 2006), compared to the present approach in which we consider that several waves (of different scales) may be present at the same place and time. We shall thus correct for this effect, simply dividing P by 2.…”
Section: Wave Breakingcontrasting
confidence: 68%
“…Consistency of this feature has been confirmed by further investigations of the Lake George wave breaking data by independent means (Babanin and Young, 2005;Manasseh et al, 2006) where the two-phase behaviour of the spectral dissipation has also been obtained.…”
Section: Polnikov (1993) Suggested Another Type Of An After-breaking supporting
confidence: 59%
“…A passive acoustic method of detecting individual bubble-formation events developed by Manasseh et al (2006) was found promising for obtaining both the rate of occurrence of breaking events at different wave scales and the severity of wave breaking. A combination of the two should lead to direct estimates of the spectral distribution of wave dissipation.…”
Section: Polnikov (1993) Suggested Another Type Of An After-breaking mentioning
confidence: 99%
“…The most successful so far were methods based on remote sensing, either by bubble-acoustic means (Manasseh et al, 2006) or whitecap observations (Melville andMatusov, 2002, Gemmrich et al, 2008). Both of these methods, however, appear to be affected in the polar seas.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%